Perbandingan Efektivitas Antara Akupunktur PC-6 dan Ondansetron dalam Mencegah Insidensi Mual dan Muntah Pasca Bedah Ortopedi - Utomo, Anggarda Kristianti; Sudirman, Syarif; Syafi’i, Imam (Jurnal Kedokteran Indonesia, 2009)
Background: Post Operative Nausea and Vomiting (PONV) has recently received increasing attention among anesthesiologists since it causes discomfort and danger to unconscious patient. It was hypothesized that acupuncture of PC-6 administered before anesthesia induction may reduce nauseavomiting incident. Ondansetron has been known as âgold standardâ anti-emetic. This study aimed to examine the relative effectiveness acupuncture to ondansetron as pre-medical anesthesia in avoiding PONV incident.Methods: This was an experimental study. The population of the research is surgical patient in IBS (Instalasi Bedah Sentral) RSO Prof Dr. R. Soeharso, Surakarta. A sample of 30 patients were assigned to two groups, 15 patients received acupuncture PC-6, and another 15 received 4 mg ondansetron. The data were analyzed using chi square.Results: One patient from acupuncture group and 2 patients from ondansetron group experienced nausea-vomiting in the first 30 minutes. Statistical analysis showed no significant difference between acupuncture PC-6 and ondansetron in preventing PONV incident.Conclusion: The acupuncture effectiveness is equal to that of ondansetron, so that it can be used as alternative anesthesia for preventing PONV incident. Jurnal Kedokteran Indonesia: 1 (1): 25-31Keywords: acupuncture, ondasetron, PONV